The portrait of contemplative women by Philo of Alexandria: the ʽtherapeutridesʼ (Circe de clásicos y modernos, 2022)
In De vita contemplativa, Philo of Alexandria describes a pious group of Hebrew philosophers. They established their residence in a small village near Lake Mareotis, outside Alexandria. The members of the congregation, called Therapeutae because of their dedication to the cure or care of souls, were both male and female. They lived in isolation from each other in small, humble houses, although on special occasions they had moments of fraternal contact. The presence of women in a regime of equality with men is one of the most striking and original features of this unique Jewish ascetic community.
Keywords: therapeutae; therapeutridae; contemplative life; community